Caracterização espectroscópica e ensaios químico - biólogicos de H2(TNBPyP) e Zn(TPPS4) visando utilização em terapia fotodinâmica - Silva, Jeanine Domareski da (2009)
The investigation of properties of porphyrin derivatives is of great importance, since they have many applications, one being the use as photo sensitizers in photodynamic therapy (PDT). We studied the free base porphyrin, cationic, bromide of 5, 10, 15, 20 - tetrakis (N-4-nitrobenzyl-4-pyridyl) porphyrin, H₂(TNBPyP) and metaporphyrin, sodium salt of 5, 10, 15, 20 - tetrakis (4-sulfonatophenyl) zinc porphyrin (II), Zn(TPPS₄), to evaluate the possible application in PDT. Through analysis of molecular absorption UV-Vis, we investigated the interaction with surfactants, the reactions of photo bleaching, the generation of singlet oxygen and the ability to aggregate in different proportions water/ethanol. The photodynamic action of these compounds was analyzed by in vitro tests with microorganisms; tests were carried out with Arthemia saline and the Staphylococcus aureus. The System used was of LEDs of different emission bands (red, orange and green) for illumination of the samples in the tests for the evaluation of the photodynamic action. First, we analyzed the spectral behavior of porphyrin H₂(TNBPyP), with the variation of pH in water and ethyl acetate/phosphate and in the presence of surfactant HPS (Zwitterionic), SDS (anionic) and CTAB (cationic). It was observed that porphyrin is stable in a wide range of pH in the various systems studied. The spectral behavior of porphyrin mixtures H₂(TNBPyP) in water/ethanol in different proportions indicated that there was no clustering in the concentration range examined. Analysis of photo bleaching was performed for the two porphyrins in light of LED systems for the total of 1 hour; it was observed that both porphyrins are photo-stable under the conditions studied. As the generation of singlet oxygen, observed through the test of uric acid, it was found that the H₂(TNBPyP) showed a higher photodynamic activity (PA) than Zn(TPPS₄). The results of microbiological tests showed that the highest mortality rate of A. saline occurs in the presence of porphyrin H₂(TNBPyP) and under illumination with red LED, indicating photodynamic action of porphyrin. In tests with the bacterium Staphylococcus aureus, we observed the effects of photodynamic action for the two porphyrins examined and the two types of LEDs tested, and the best results were obtained by photo inactivation under lighting time of 30 minutes. Thus, the results show that the porphyrins tested have potential for the use in Photodynamic Therapy.